2015
DOI: 10.1007/s00338-015-1318-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing environmental correlates of fish movement on a coral reef

Abstract: Variation in dispersal and movement patterns of coral reef fishes is likely linked to changes in environmental conditions. Monitoring in situ environmental parameters on coral reefs in conjunction with the movements of fishes can help explain the relationship between exploited populations and their environment. Sixty adult Lethrinus miniatus were acoustically tagged and monitored along a coral reef slope for up to 1 yr. Individuals occurred more often on the reef slope during days of cooler temperatures, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…The focus of this study was on providing new insights into the variability of visits by transient predators to patch reefs, but these data also provide indications of the potential effects of environmental change. Firstly, temperature is likely to be at least partly causing the seasonal variation seen in some of the species and warmer sea‐surface temperatures under global climate change scenarios may affect the movement of transient predators (Currey et al ., ). The consequences on fish abundances of clearing mangrove nursery and foraging habitats have frequently been stated (Valiela et al ., ) and the present study also suggests that changes to the distribution of transient predators may occur if inshore habitat connectivity is affected by coastal development.…”
Section: Discussionmentioning
confidence: 97%
“…The focus of this study was on providing new insights into the variability of visits by transient predators to patch reefs, but these data also provide indications of the potential effects of environmental change. Firstly, temperature is likely to be at least partly causing the seasonal variation seen in some of the species and warmer sea‐surface temperatures under global climate change scenarios may affect the movement of transient predators (Currey et al ., ). The consequences on fish abundances of clearing mangrove nursery and foraging habitats have frequently been stated (Valiela et al ., ) and the present study also suggests that changes to the distribution of transient predators may occur if inshore habitat connectivity is affected by coastal development.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, fish abundances can be closely linked to patches that best match their immediate habitat requirements, explaining why the best habitat predictors of juvenile abundance are during the winter, when this size class is most prevalent. Adult lethrinids are known to move when environmental conditions become unfavorable (Currey et al ) and have average home ranges of 8.5 km 2 at Ningaloo (Pillans et al ). Although recruits may be relatively site‐attached, young fish could be capable of moving among patches to find more suitable habitat, potentially uncoupling local recruitment and juvenile abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Currey et al [37] reported that the abovementioned 26 acoustically tracked Lethrinus miniatus tended to occur more often on the southern Great Barrier Reef slope when water temperature was cooler. Further study is needed to reveal their depth-use patterns in more detail by increasing the number of tracked fish and by specifying the purpose for visiting deeper (>30 m) areas.…”
Section: Discussionmentioning
confidence: 99%